2016
DOI: 10.21833/ijaas.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transcription factor NF-KAPPA B/P65 and cyclooxygenase-2 (COX-2) in testicular damage induced by Red Bull energy drink in rat

Abstract: The risks of heavy consumption of energy drinks have become a significant health problem. Concerns have been raised about the adverse health effects of these products. This study was performed to investigate the possible histopathological and immunohistochemical changes in the testis induced by excessive and prolonged consumption of Red Bull, one of the most consumed energy drinks all over the world, in rats and the possible mechanism of such changes. Thirty adult male albino rats were randomly allocated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated histopathological lesions in different organs following administration of energy drinks. These organs include liver (Khayyat et al, 2012), kidney, brain (Salih et al, 2018), testis (Dias et al, 2015;Ahmed, 2016), pancreas and fundus of stomach (Ayuob and ElBeshbeishy, 2016), gastric and duodenal mucosae (Mohamed et al, 2018).…”
Section: *Total Protein In Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated histopathological lesions in different organs following administration of energy drinks. These organs include liver (Khayyat et al, 2012), kidney, brain (Salih et al, 2018), testis (Dias et al, 2015;Ahmed, 2016), pancreas and fundus of stomach (Ayuob and ElBeshbeishy, 2016), gastric and duodenal mucosae (Mohamed et al, 2018).…”
Section: *Total Protein In Serummentioning
confidence: 99%
“…Reactive oxygen species (ROS) are likely involved in the pathogenesis of wide variety of human diseases. ROS are very harmful and may cause direct damage to vital cell constituents such as proteins, lipids, and deoxyribonucleic acid (DNA) (Ahmed, 2016).…”
Section: *Total Protein In Serummentioning
confidence: 99%
“…These lesions could be attributed to imbalance of oxidant/antioxidant environment in these tissues with increased oxidant stress as a result of reactive oxygen species production. Reactive oxygen species (ROS) are very harmful causing direct damage to vital cell components as lipids, proteins and deoxyribonucleic acid (DNA) [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation of chondrocytic cells produced phosphatidylinositol 3-kinase (PI-3K)/protein kinase B (Akt), mitogen-activated protein kinase (MAPK) and nuclear factor-B (NF-B) leading to activation of the multiple pro-inflammatory signaling pathways (Ahmed 2016). On the other hand, the use of rutaecarpine as a treatment module prevented the rise of IL-1, TNF-, IL-6, cyclooxygenase-2 (COX-2) and matrix metalloproteinases (MMPs) during inflammatory reaction.…”
mentioning
confidence: 99%